Destination Tokyo [videorecording (DVD)] - Daves, Delmer, 1904-1977; Daves, Delmer, 1904-1977; Grant, Cary, 1904-1986; Garfield, John; Hale, Alan, 1892-1950 (Warner Home Video : Turner Entertainment Co., 2004)
Twenty-four hours out of San Francisco, submarine captain Cassidy unseals his top-secret orders and reads two fateful words: Destination Tokyo. Set during the second World War, depicts the story of a submarine and its crew as they sail to Tokyo, Japan to sink Japanese warships.